QUALITY OF CUSTOMER SERVICE, LOCATION AND PRICE PERCEPTION OF PURCHASING DECISIONS (Study On Bebek H Pak Slamet Banyumanik Semarang) - Endang Tri Widyarti; Dian Triyani; M Sigit Taruna (Fakultas Ekonomi Universitas Pekalongan, 2021)
This research determines differences in Quality Control Consumer, Location, and price perception of purchasing decisions. This research was carried out in another Bebek H Pak Slamet. Respondents using non-random sampling techniques. This sampling technique uses purposive sampling technique, with the following criteria: consumers or customers who are at least 17 years old, consumers or customers who have consumed other Bebek H Pak Slamet Banyumanik Semarang products and have already visited Bebek H Pak Slamet Banyumanik Semarang. The technique of data collection uses a questionnaire that has been tested for validity and reliability. Data analysis in this study uses multiple linear regression analysis which aims to test the variables of Quality Control Cosumen, Location and price perception of purchasing decisions. The results showed that Quality Control Consumer had an effect, Location, and price perception had a positive and significant effect on purchasing decisions